IMPLEMENTASI MODEL PEMBELAJARAN EXPERIENTAL LEARNING DI SEKOLAH ALAM JOGJA GREEN SCHOOL DAN DAMPAKNYA DALAM MENUMBUH KEMBANGKAN NILAI KARAKTER SISWA - Novalinda Dhea Amelia; Deftya Salfa Nurrochmah; Fatwa Saputri; Muhammad Choirul Musthofa; Nafaisya Kumala Sandy; Wahyuni Rismawati; Abdurrahman Asy’ari; Taufik Muhtarom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to conduct a comprehensive analysis at Sekolah Alam Jogja Green School to: (1) determine the implementation of the experiential learning model in the school; (2) identify the character values developed through the implementation of the experiential learning model; and (3) examine the impact of implementing the experiential learning model on students’ character development. The method used was field research conducted on October 28, 2025, located in Dusun Jambon, RT 04/RW 22, Trihanggo Village, Gamping District, Sleman Regency, Special Region of Yogyakarta. A qualitative approach was employed, involving observation, in-depth interviews, and documentation as data collection techniques. The results show that the implementation of the experiential learning model at Sekolah Alam Jogja Green School provides active, hands-on learning experiences through activities that engage students physically, emotionally, and intellectually. The application of this learning model successfully fosters character values such as love for nature, entrepreneurship, independence, morality, logic, and science. The positive impact of experiential learning is evident in students’ behavioral changes, as they become more independent and responsible in their daily school activities. Based on these findings, the experiential learning model is recommended as an effective instructional strategy for character development in schools that emphasize experience-based and environmental education.